Nuclear Medicine in Prostate Cancer: A New Era for Radiotracers - Cuccurullo, Vincenzo (World J Nucl Med, 2018)
Natural history of prostate cancer (PCa) is extremely variable, as it ranges from indolent and slow growing tumors to highly aggressive histotypes. Genetic background and environmental factors co-operate to the genesis and clinical manifestation of the tumor and include among the others race, family, specific gene variants (i.e., BRCA1 and BRCA2 mutations), acute and chronic inflammation, infections, diet and drugs. In this scenario, remaining actual the clinical interest of bone scan (BS) in detecting skeletal metastases, an important role in diagnostic imaging may be also carried out by, positron emission tomography/computed tomography (PET/CT) and PET/magnetic resonance imaging (PET/MRI), which combine morphological information provided by CT and MRI with functional and metabolic data provided by PET acquisitions. With respect to PET radiotracers, being ancillary the usefulness of F-18 fluoro-deoxyglucose and not yet demonstrated the cost-effectiveness of F-18 Fluoride respect to BS, the main role is now played by choline derivatives, in particular by 11C-choline and 18F-fluorocholine. More recently, a greater interest for both diagnostic and therapeutic purposes has been associated with radiotracers directed to prostate-specific membrane antigen (PSMA), a transmembrane protein expressed on the cell surface, which showed high selective expression in PCa, metastatic lymph nodes and bone metastases. Several PSMA-targeted PET tracers have been developed many of which showing promising results for accurate diagnosis and staging of primary PCa and re-staging after biochemical recurrence, even in case of low prostate specific antigen values. In particular, the most widely used PSMA ligand for PET imaging is a (68)Ga-labelled PSMA inhibitor, (68)Ga-PSMA-HBED-CC ((68)Ga-PSMA-11). (99m)Tc-HYNIC-Glu-Urea-A for single photon emission computed tomography, and (177)Lu-PSMA-617 for radioligand therapy has also been applied in humans, with interesting preliminary results related to a possible theranostic approach. A potential role of PSMA radioligands in radio-guided surgery has also been proposed.